Predictive Modeling of the Kinetics of Deactivation of Liquid-Phase Alkylation of Hydrocarbons Processes - Ivanchina E. D. Emilia Dmitrievna; Ivashkina E. N. Elena Nikolaevna; Dolganova I. O. Irena Olegovna; Chuzlov V. A. Vyacheslav Alekseevich; Kopycheva U. N. Uljyana Nikolaevna; Ivanchin N. R. Nikita Ruslanovich (2021, 2021)
Title screen